Cycling Media and Collectives. Cycling Vlogs and Mobile Infrastructures - Julia Bee (SHARE Press, 2022)
Not only have cycling communities produced a visual culture consisting of photography, videos, fashion, art and bikes themselves. Conversely, images and videos produce and shape cycling culture and therefore communities. Aesthetics in the digital culture thus contribute to the complex of cycling mobility. In this paper, I concentrate on cycling vlogs as part of mobile infrastructure. Cycling vlogs cultivate a "social aesthetic" (Born et al., 2017) that adapts symbols from cycling culture, hereby bringing into circulation, and thus shaping, cycling practices. Nevertheless, the interconnection of different platform media like Youtube and performance apps makes digital cycling cultures a place of data production and harvesting of different sorts.